Amerind ancestry, socioeconomic status and the genetics of type 2 diabetes in a Colombian population. - Campbell, D; Parra, M; Duque, C; Gallego, N; Franco, L; Tandon, A; Hünemeier, T; Bortolini, C; Villegas, A; Bedoya, G; McCarthy, M; Price, A; et al. (Public Library of Science, 2012)
The "thrifty genotype" hypothesis proposes that the high prevalence of type 2 diabetes (T2D) in Native Americans and admixed Latin Americans has a genetic basis and reflects an evolutionary adaptation to a past low calorie/high exercise lifestyle. However, identification of the gene variants underpinning this hypothesis remains elusive. Here we assessed the role of Native American ancestry, socioeconomic status (SES) and 21 candidate gene loci in susceptibility to T2D in a sample of 876 T2D cases and 399 controls from Antioquia (Colombia). Although mean Native American ancestry is significantly higher in T2D cases than in controls (32% v 29%), this difference is confounded by the correlation of ancestry with SES, which is a stronger predictor of disease status. Nominally significant association (P<0.05) was observed for markers in: TCF7L2, RBMS1, CDKAL1, ZNF239, KCNQ1 and TCF1 and a significant bias (P<0.05) towards OR>1 was observed for markers selected from previous T2D genome-wide association studies, consistent with a role for Old World variants in susceptibility to T2D in Latin Americans. No association was found to the only known Native American-specific gene variant previously associated with T2D in a Mexican sample (rs9282541 in ABCA1). An admixture mapping scan with 1,536 ancestry informative markers (AIMs) did not identify genome regions with significant deviation of ancestry in Antioquia. Exclusion analysis indicates that this scan rules out ~95% of the genome as harboring loci with ancestry risk ratios >1.22 (at P < 0.05).